Pengaruh Efektivitas Pembelajaran Dengan Menggunakan Google Classroom Terhadap Hasil Belajar Siswa di MAN 02 Kepahiang - Meti Herlina; Oktavian (PendIPA Journal of Science Education, 2023)
The aim of this study was to determine the effect of the effectiveness learning using google classroom on student learning outcomes at MAN 02 Kepahiang. The population used in this study were all students of class XII MIA MAN 02 Kepahiang. The sample used is class XII MIA 3. With a total of 35 students using a random technique, namely the class has the same opportunity or opportunity to be sampled. Data collection techniques used are questionnaires and documentation. Data analysis technique with the help of SPSS version 21 program. Based on the results of data analysis, it can be said that the effectiveness of learning by using google classroom simultaneously affects learning outcomes in class XII MIA 3 students at MAN 02 Kepahiang for the academic year 2020/2021 simultaneously 67% and the rest is influenced by other factors. From these results indicate that the value of the two variables has a positive effect on student learning outcomes.